Advanced Green Technologies Toward Future Sustainable Energy Systems - Aziz, Muhammad (Indonesian Journal of Science and Technology, 2019)
Currently, the usable energy is basically harvested from the fossil energy sources, including coal, oil, and gas, which are believed to harm the environment due to the emitted GHGs. The awareness to the climate change and limited reserve of fossil energy sources has led to a strong motivation to develop a new energy system which can facilitate three important pillars: security, clean environment, and economic opportunity. This future energy system is strongly expected to be able to blend both fossil and renewable energy sources, while minimize its environmental impacts. To realize it, the primary energy sources are converted to the efficient secondary energy sources, including electricity and hydrogen. These two kinds of secondary energy source are considered very promising in the future, following a high demand in many sectors. In transportation sector, both electricity and hydrogen are believed to become the future fuels as the deployment of electric and fuel cell vehicles is increasing rapidly. In this paper, several potential technologies to produce the energy cleanly from primary energy sources are introduced and evaluated. In addition, clean and efficient technologies in storage and utilization are also described.